Assessment of Dietary Intake, Energy Status, and Factors Associated With RED-S in Vocational Female Ballet Students - Civil, Rita; Lamb, Antonia; Loosmore, Diana; Ross, Louisa; Livingstone, Kerry; Strachan, Fiona; Dick, James R.; Stevenson, Emma J.; Brown, Meghan A.; Witard, Oliver C. (Frontiers in Nutrition, 2019)
Elite ballet dancers are at risk of health issues associated with Relative Energy Deficiency in Sport (RED-S). This study determined the nutritional status, estimated energy status, and assessed factors related to RED-S in vocational female ballet students. Using a cross-sectional study design, we measured dietary intake (food diaries and 24 h dietary-recall) and energy expenditure (accelerometry) in vocational female ballet students (n = 20; age: 18.1 ± 1.1 years; body mass index: 19.0 ± 1.6 kg·m2; body fat: 22.8 ± 3.4%) over 7 days, including 5 weekdays (with dance training) and 2 weekend days (without scheduled dance training). Furthermore, we assessed eating behaviors, menstrual function, risk of RED-S (questionnaires), and body composition (dual x-ray absorptiometry). Energy and macronutrient intakes of vocational ballet students were similar during weekdays and weekend days (P > 0.050), whereas total energy expenditure was greater on weekdays than weekend days (P < 0.010; 95% CI: 212, 379). Energy balance was lower on weekdays (−425 ± 465 kcal·day−1) than weekend days (−6 ± 506 kcal·day−1, P = 0.015; 95% CI: −748, −92). Exercise energy expenditure was greater on weekdays (393 ± 103 kcal·day−1) than weekend days (213 ± 129 kcal·day−1; P < 0.010; 95% CI: 114, 246), but energy availability was similar between time periods (weekdays 38 ± 13 kcal·kg FFM·day−1; weekend days 44 ± 13 kcal·kg FFM·day−1; P = 0.110). Overall, 35% of participants had an energy intake <1,800 kcal·day−1, 44% had reduced energy availability (30–45 kcal·kg FFM·day−1), and 22% had low energy availability (<30 kcal·kg FFM·day−1). Menstrual dysfunctions were reported in 40% of participants; 15 and 25% reported oligomenorrhea and secondary amenorrhea, respectively; while 65% were classified at risk of RED-S (based on the Low Energy Availability in Females Questionnaire). All participants had adequate bone health (bone mineral density Z-score: 1.1 ± 0.9 SD), but 20% had <85% expected body weight. The observation of an energy deficit in vocational female ballet students was primarily attributed to an inability to plan energy intake and thereby meet higher energy requirements during ballet training weekdays. Screening for factors associated with RED-S and tailoring education programs to inform energy and nutrition requirements for health and training are recommended in elite young ballet students.